The Influence of Labeling , Price, and Quality Product on Purchasing Decisions and Interest in Buying Sunscreen Makassar City Community - Gemy Nastity Handayany; Nurul Magfirah (International Journal Of Health Science, 2025)
Rapid progress in Makassar City increases awareness will importance protect skin from effect bad ultraviolet light with use sunscreen . The height request will sunscreen , has produce various types and products sunscreen so that an effective marketing strategy is needed in increase decision purchase sunscreen in the community in Makassar City. Research This aiming For know influence labeling , price , and quality product to decision purchase sunscreen and its effects to interest buy repeat product sunscreen in the community in Makassar City. Research This is study descriptive with approach quantitative , using questionnaire as tool help For data collection with sample totaling 100 people. Observed variables covering Labeling (X1), Price (X2), Quality Product (X3), Purchase Decision (Y1) and Purchase Interest (Y2). Data analyzed use SmarPLS 4.0. Research results show that the most influential factor decision purchase is Quality Product with loading factor 0.387 then followed with Labeling with loading factor 0.339, while price No influential significant to decision purchases and decisions purchase influence level interest buy repeat product with loading factor 0.603. So can concluded that Labeling and Quality Product influence Purchasing Decisions which have an impact on the Purchasing Interest of the community in Makassar City.